The Effects of Service Quality and Price on Customer Satisfaction at the Auto 2000 Office Medan Amplas Branch, North Sumatra - Ridwan; Julianto Hutasuhut (Garuda Prestasi Nusantara Consulting, 2022)
This study intends to examine how customer satisfaction at the Auto 2000 office's Medan Amplas Branch is impacted by service quality and cost. Descriptive quantitative research has been selected as the method. 96 clients served as the study's sample population. A questionnaire is used as the data collecting method, and the results are evaluated using SPSS software based on the validity test, reliability test, and classical assumption test. The multiple linear regression test, the t test, the F test, and the coefficient of determination test were utilized in the data analysis technique (R2 test). According to the t test results, the service quality variable has a stronger impact on customer satisfaction than the price variable because its t count value is higher 4,300 than the pricing variable's t value, which is 3,051. The estimated F value, which is 568,732, is more than the 2,700 F value in the table. This demonstrates that the customer satisfaction variable is significantly and positively impacted by both the service quality and pricing. The adjusted R Square value of the coefficient of determination test findings was 0.923, or 92.3 percent. The percentage of service quality and price that can explain customer satisfaction is very high, at 93.3 percent, while the remaining 7.7 percent is influenced by other variables not examined in this study. This means that the variation in the relationship between service quality and price variables with customer satisfaction can be classified as very high.